Cross-asset return predictability: Carry trades, stocks and commodities. (June 2016) - Lu, Helen; Jacobsen, Ben
Highlights: Equity returns predict the short leg profits of carry trades. Commodity price changes predict the long leg profits. Consistent with gradual information diffusion instead of time-varying risk. One-directional predictability from commodities to stocks and stocks to currencies. Abstract: Equity returns predict carry trade profits from shorting low interest rate currencies. Commodity price changes predict profits from longing high interest rate currencies. The gradual information diffusion hypothesis (Hong & Stein, 1999) provides a ready explanation for these predictability results. These results cannot be explained by time-varying risk premia as stock returns and commodity price changes significantly predict negative carry trade profits. The predictability is one-directional, from commodities to high interest rate currencies, from commodities to stocks and from stocks to low interest rate currencies.